PERUBAHAN SIFAT FISIK DAN KIMIA GETUK TRI WARNA SELAMA PENYIMPANAN PADA SUHU KAMAR - , ATHILLAH NURHASANAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Getuk Tri warna is a traditional food of Central Java community, especially magelang area. Getuk Tri warna made of crushed and steamed cassava and other additives. Getuk Tri warna has sugar dan high fat content and thus susceptible to damage and has a short shelf life . This study aims to determine the physical and chemical changes getuk Tri warna during storage at room temperature. Physical changes include changes in texture, color and aw values, where as chemical changes include changes in water content, total sugar content, fat content, total acid, and free fatty acid levels. Getuk Tri warna in cardboard packaging obtained from a souvenir shop in Magelang then stored in the open air, at a mean temperature of Â±270C and Â± 69% RH conditions the same as in the store. GetukTri warna observed on the storage to1, 3, 5, 7, and 9 to analyze physical (texture, color, and aw) and chemical (moisture, fat, total sugars, total acids, and free fatty acids). The results showed that there was a physical and chemical changes during storage getukTri warna. Levels of free fatty acids (FFA), total acid, the value of the texture (hardness, adhesiveness, resillience), and getuk Tri warna aw value increased during storage. While the color values (L*a*b*), moisture content, fat, and total sugar decreased.